Characterisation of Productivity Traits of Sahiwal - Friesian Breed Groups - Md. Alimuddin Talukder, Md.Azharul Islam Talukder (2002)
The dairy industry in Malaysia is mainly dependent on imported milk and milk products. The self-sufficiency for dairy product is 4.5%. In an effort to boost the local dairy industry, the government through the Department of Veterinary Services embarked on a crossbreeding project using 50% Sahiwal - 50% Friesian crossbreds imported from Australia and New Zealand. Through inter se mating and backcrossing, a number of Sahiwal - Friesian crossbred groups with 50 - 75% Friesian genes have been produced. This study was carried out to evaluate some of the genetic and nongenetic factors influencing milk production and reproductive performances of these Sahiwal - Friesian breed groups. This study focused on the dairy unit at the Ladang Pusat Temakan Haiwan Air Hitam in lohor. Eight breed groups were evaluated, namely M50, M50-1, M50-2, M50-3, M56, M63, M75 and M75-1. Retrospective data on milk production an d female reproductive traits of 1585 cows, born between 1981 and 1999, were evaluated. The composition and quality of milk from 180 cows from six of the breed groups and at three stages of lactation was also analysed. M7S-1 had the highest mean for milk yield per day (MYD) (S.87 - 6.69 kg), milk yield l20 days (MYl20) (70S- 803 kg), total lactation milk yield (TLDM) (1678 kg), milk yield 30S days (MY30S) (1819 kg), lactation length (LL) (261 days), peak milk (PM) (9.93 kg) and days to peak milk (DPM) (49 days). It also had the shortest dry period (DP) (18S days). However, this breed group was not significantly different from M7S, MS6 and M50-3 for these traits. Maternal additive genetic effects of Friesian genes on MYD, MY120, MY305, TLDM, LL and PM were generally significant (P<0.05) and favorable. However, maternal heterosis was negative (P<0.05) for TLDM, LL and DPM. Individual heterosis was significant (P<0.05) only for MY30S. Individual and maternal additive and individual heterotic effects were non significant for DPM and DP. The inverse polynomial function gave a better fit to the lactation data compared to the gamma curve for the breed groups (R2: 0.27 - 0.54 vs 0.11 - 0.37). With respect to milk composition and quality the effect of breed group was significant (P<0.05) only for total acidity (TA). The quality of milk from these Sahiwal - Friesian breed groups met the required standard.